POSITIVE PREDICTIVE VALUE OF TRANSCRANIAL ULTRASOUND IN EVALUATION OF HYPOXIC-ISCHEMIC ENCEPHALOPATHY KEEPING MRI AS A GOLD STANDARD - SOHAIL , M; SARWAR , S; ZAIDI , H (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Department of Radiology, Combined Military Hospital, from January 2023 to June 2023 to compare the diagnostic accuracy of TUCS and MRI to assess HIE and evaluate the pros and cons of both imaging modalities. A total of 50 neonates were included in the study. All patients underwent physical examination, and detailed history was recorded. MRI and TCUS were performed on all patients. Results showed that 33 of 50 patents were diffusion restricted. Thirty-two cases were TCUS positive, and 18 were TCUS negative. Correlated to DWI, its sensitivity was 88.3%, specificity 100%, positive predictive value (PPV) 100%, negative predictive value (NPV) 79%, and diagnostic accuracy 91.7%. Among 48 MRS-positive patients, 41 were TCUS-positive, and 9 were negative. Correlated to MRS, its sensitivity was 89.5%, specificity 100%, PPV 100%, NPV 28.7%, and diagnostic accuracy 90%. TCUS is a simple imaging modality with good sensitivity for periventricular leukomalacia and hemorrhage. However, its less sensitive and detection of lesions of the brainstem and cerebral convexity. MRI has higher specificity and sensitivity for detecting injury caused by HIE. It provides soft tissue contrast and information about the site and extent of injury.